LANGUAGE LEARNING STRATEGY AND STUDENTS’ WRITING SKILL ACHIEVEMENT: A CORRELATIONAL RESEARCH - Nurdianingsih, Fitri (University of Kuningan, 2018)
Since writing is fundamental in learning to think and express one’s thoughts in ways that reach others, the ability to use language coherently and powerfully and to wrtite in ways that connect with others across cultural boundaries and within communities is essential to active citizenship and to success in almost any profession. The problem of the study was to know whether or not there was a significant correlation between students’ learning strategy and their writing skill achievement of the second semester students at IKIP PGRI Bojonegoro. This research was a correlational research. The instruments used in this research were writing test and learning strategy questionnnaire. Then, the correlation of the data was calculated by using Pearson Product Moment Formula. The result showed that there is a correlation between students’ learning strategy and their writing skill achievement of the second semester students at English Education Department of IKIP PGRI Bojonegoro in academic year 2016/2017. Keywords: Learning strategy; writing skill; achievement; correlational research.